Virtual networks dependability assessment framework. (2017) - Al-Rubaiey, Baker; Abawajy, Jemal H.
Advances in virtualisation technology have enabled the development of network virtualisation that complements server virtualisation by enabling continuous workload agility irrespective of the network addressing and protocol of the underlying physical network. Despite huge benefits both in cost and accessibility, network virtualisation is susceptible to failure due to a wide variety of factors. Therefore, dependability in a virtualised network environment is a significant issue that need to be addressed before the full benefits of network virtualisation can be exploited. In this paper, we propose a framework to estimate dependability risks in virtual network environments considering variations in the virtual network configurations. The proposed framework uses the reliability block diagram (RBD) and continuous time Markov chains (CTMC) to model and analyse the dependability level of a virtual network. The proposed framework is helpful to the design and construction of more dependable VNE.